Human Eb Peptide: Not just a By-product of Pre-pro-IGF1b Processing? - Durzyńska, J.; Wardziński, A.; Koczorowska, M.; Goździcka-Józefiak, A.; Barton, E. R. (Hormone and Metabolic Research, 2013)
Several physiological activities have been assigned to E-peptides derived from pre-pro-insulin-like growth factor (IGF1) processing; however, the whole range of the E-peptides’ functions is still unknown. The objective of this study was to investigate human Eb peptide (hEb) in terms of its bioactivity, cellular localization, and intracellular trafficking using human cancer cells. Human Eb fused with red fluorescence protein (RFP) or green fluorescence protein (GFP) localizes strongly to nucleoli and to a lesser extent to nuclei of HeLa and U2-OS cells. Mutagenesis of hEb nucleolus localization sequence (NoLS) leads to its partial delocalization from nuclei and nucleoli to cytoplasm of transfected cells. Thus, NoLS is not sufficient for the hEb to be localized in nucleoli of the cells and a different mechanism may be involved in hEb targeting. A BrdU ELISA showed that the proliferation index of cells expressing hEb hybrid proteins increased up to 28%. For comparison, the same assay was performed using HeLa cells treated extracellularly with synthetic hEb. A significant increase in the proliferation index was observed (41–58% for concentrations ranging from 10–100 nM, respectively). Additionally, a cell migration assay was performed using stable U2-OS cell lines expressing hEb fused with RFP or RFP alone as a negative control. The migration index of hEb expressing cells was 38.3% greater. The increase in cell proliferation index and in motile properties of hEb expressing cells demonstrate that hEb is more than a pre-pro-IGF1b processing product, and has intrinsic activity of biological significance.
Keywords: NoLS; nucleolus; protein trafficking; stable cell lines; proliferation and motility index